Sense of Belonging Among Undergraduate Students at The American University in Cairo: Demographic Trends, Barriers and Facilitators - Mohamed, Lamiaa M. (AUC Knowledge Fountain, 2026)
A sense of belonging is widely recognized as a key determinant of undergraduate students’ academic success, well-being, and persistence in higher education. However, existing research is largely grounded in Western contexts and often emphasizes institution-level measures, with limited attention to how belonging is experienced and constructed by students in non-Western settings. This study examines undergraduate students’ sense of belonging at the American University in Cairo, focusing on factors that shape belonging and institutional practices that may strengthen it. Using a sequential mixed-methods design, the study examined 87 responses from a quantitative survey adapted from the University Belonging Questionnaire, followed by five phenomenological interviews to explore students’ lived experiences and contextualize the quantitative results. The study concludes that sense of belonging is a dynamic, co-constructed process shaped by the interaction between institutional structures and student agency. It proposes targeted, evidence-based interventions centered on faculty engagement, localized academic communities, inclusive governance, and developmentally informed support. It also expands dominant belonging frameworks by highlighting moral and procedural dimensions that go beyond social integration and peer relationships.